Theorising South Africa’s Corporate Governance - West, Andrew (Journal of business ethics, 2006)
South Africa’s principal corporate governance report aspires to an ‘inclusive’ approach to corporate governance, in which companies are clearly advised to consider the interests of a variety of stakeholders. Yet, in common with many other countries, there is little discussion of the theoretical foundations and assumptions implicit in the recommended approach to corporate governance. The purpose of this article is to provide an analysis of corporate governance and the corporate environment in South Africa in terms of existing theory and models of corporate governance, and to provide a critique based on a consideration of traditional African values and the socio-economic necessities of post-apartheid South Africa. The result is the identification of an incompatibility between the current corporate environment in South Africa and the given exposition of African values. Some prospects for change are then identified.